PERANCANGAN SISTEM INFORMASI PERSEDIAN BAHAN BAKU DI PT SINAR SAKTI MATRA NUSANTARA - Arif Noor Iman; Paulus Prasetyo Lumbansiantar; Nurdiansyah Permana; Erdy rezki putra; Dani Kosasih (Universitas Widyatama, 2023)
The supply of materials is a very important part in a business, it aims to help the companies improve or provide the maximum service to costumers, and therefore the use of the fast information system entry and exit of materials needed by the company, time and accuracy in the sense of the information is required for the processing. The study was aiming to learn what is happening in the company and it is the anticipation to prevent the worst thing. The problem solution above solved by using waterfall method which using tools like a document flow diagram, context diagram, data flow diagrams, and database design using entity relation diagram, normalization and relation table. Meanwhile the data collection method used is the method of collecting primary data that source using the method of observation and interview while secondary data sources taken from the library data. The material supply information system is built as a solution of the problems that arise when the system is still using manually. The information system material supply is capable to processing data quickly, it can shorten the search process of the data and supporting the service needs precise and accurate information for the company. Keywords: Materials Stocks, Structured, Information System